The Effect of Provider Perception about Satisfaction of Capitation System - Siyoto, Sandu (University of Muhammadiyah Malang, 2016)
Capitation funds distributed by BPJS to health services is providers of health care in FKTP receive regular income per participant, per period of time for which the service has been determined. From the initial survey results were done, there are some respondents who are not satisfied with the capitation system. The purpose of this study was to investigate the effect of provider perception about satisfaction of capitation system.The design study is a quantitative research using a